METONYMY OF THE WORD ‘INDONESIA’ IN PHRASES ‘PROUD OF INDONESIA’ USED ON FACEBOOK - Jennifer Jennifer; Paulus Tri Nugroho Putro; Victory Cahya Adi (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
Simply defined, metonymy is a phenomenon in which two things are associated, so that one thing stands for the other, i.e. the source stands for the target. (Evans and Green, 2006, p. 314; Barcelona, 2003) The example from Evans and Green (2006, p. 312) is “England beat Australia in the 2003 rugby World Cup ?nal.” In that example, England and Australia stand for their own national football teams. The example is whole-for-part metonymy. Generally classified, the types of metonymy are whole for part and part for whole. (Barcelona, 2003, p. 239) What it means by “whole for part” is a general thing represents a specific thing. It goes the other way around for “part for whole”. As everyone uses metonymy very often, it is everyone’s awareness towards metonymy that should be increased. Metonymy is a powerful tool (Guan, 2009, p. 179). It is a “cognitive tool for people’s conceptualization of the world” (Guan, 2009, p. 179) and particularly “for guiding inferencing in the interpretation of spoken discourse” (Kriskovic & Tominac, 2009, p. 50).